High-risk area for migraine attacks — a new concept in migraine pathophysiology - Rispoli, Marianna Gabriella; De Angelis, Maria Vittoria; Melchionda, Donato; Manente, Gabriele (Frontiers in Neurology, 2025)
Migraine is a common primary and often disabling neurological disorder, whose pathophysiology is still debated. It does not appear to be an isolated event of head pain but the consequence of recurrent disruption of healthy homeostasis in some brain functions. We propose a new theoretical model, focused on the existence of a “high-risk area” for migraine attacks, which can represent a potential target of non-pharmacologic treatment and prevention. We suggest that migraine arises from the combined effects of three primary factors, namely depressive or unstable mood, unrestful sleep and sympathetic-parasympathetic imbalance with parasympathetic prevalence, alongside with their temporal variability, potentially through dysfunction of homeostatic hypothalamic networks in susceptible individuals. Moreover, these three primary factors contribute to a state of low brain energy, that contains the high-risk area and represents the condition in which migraine attacks rise up. Wearable devices, self-administered questionnaires and clinical tools (i.e., polysomnography, pupillary light reflex, plasma catecholamines dosage) may be used to monitor autonomic nervous system function, mood and sleep and demonstrate the existence of the high-risk area. This will be helpful for patients to understand when they are about to enter in the high-risk area, in order to implement strategies to prevent migraine attacks. This approach would provide a significant advantage in terms of prevention and early treatment.